2023
DOI: 10.3390/mi14030521
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Vanadium Incorporated Ferrocyanides as Potential Cathode Materials for Application in Sodium-Ion Batteries

Abstract: Sodium-ion batteries (SIBs) are potential replacements for lithium-ion batteries owing to their comparable energy density and the abundance of sodium. However, the low potential and low stability of their cathode materials have prevented their commercialization. Prussian blue analogs are ideal cathode materials for SIBs owing to the numerous diffusion channels in their 3D structure and their high potential vs. Na/Na+. In this study, we fabricated various Fe-V-incorporated hexacyanoferrates, which are Prussian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…Meanwhile, the presence of V-O binding in sodium vanadium hexacyanoferrate (NaVHCF) as a SIB cathode demonstrated only one redox potential [187]. Nguyen et al reported that the presence of V-O passivated the high-spin Fe related to the low redox potential, supporting the structure of the low-spin Fe ion; therefore, NaVHCF provided a single redox potential of approximately 3.26/3.65 V versus Na/Na + [192]. However, the capacity was only approximately 70-80 mAh g −1 .…”
Section: Metal-organic Compounds: Prussian Blue Analogsmentioning
confidence: 99%
“…Meanwhile, the presence of V-O binding in sodium vanadium hexacyanoferrate (NaVHCF) as a SIB cathode demonstrated only one redox potential [187]. Nguyen et al reported that the presence of V-O passivated the high-spin Fe related to the low redox potential, supporting the structure of the low-spin Fe ion; therefore, NaVHCF provided a single redox potential of approximately 3.26/3.65 V versus Na/Na + [192]. However, the capacity was only approximately 70-80 mAh g −1 .…”
Section: Metal-organic Compounds: Prussian Blue Analogsmentioning
confidence: 99%